Digital Certificate-Based Authentication Model for Enhanced Smartphone Security - A. H. Azni; Sakiinah Altaf Hussain; Najwa Hayaati Mohd Alwi (Journal of Computing Research and Innovation)
Smartphones are integral to the Internet of Things, facilitating connectivity for various devices such as home systems and healthcare tools. However, the growing threat of identity theft, data breaches, and attacks due to weak authentication and poor password management emphasizes the critical need for mobile device security. Cryptography is pivotal in ensuring that only authorized devices can access data. This paper introduces an innovative authentication model for smartphones, integrating digital certificates and secret keys to securely encrypt and decrypt data. The model employs the RSA algorithm to generate encryption keys and authenticate user and device identities. Aimed at addressing smartphone users' authentication needs, the model operates through three phases: Registration, Digital Certificate, and Authentication, each bolstering data protection through digital certificate-based authentication. To assess the model, expert reviews are conducted to ensure its effectiveness. The results demonstrate significant improvements in security and ease of implementation compared to traditional authentication methods. Expert reviews agree that the model effectively mitigates unauthorized access risks by strengthening encryption and authentication protocols across its three key phases. These enhancements make it particularly suited for addressing the evolving security challenges of mobile applications, setting a benchmark for future authentication frameworks in smartphone ecosystems.